Impact of cancer diagnosis on causes and outcomes of 5.9 million US patients with cardiovascular admissions. (15th October 2021) - Matetic, Andrija; Mohamed, Mohamed; Miller, Robert J.H.; Kolman, Louis; Lopez-Mattei, Juan; Cheung, Winson Y.; Brenner, Darren R.; Van Spall, Harriette G.C.; Graham, Michelle; Bianco, Christopher; Mamas, Mamas A.
Abstract: Introduction: There are limited data on causes of cardiovascular (CV) admissions and associated outcomes among patients with different cancers. Methods: All CV admissions from the US National Inpatient Sample between October 2015 to December 2017 were stratified by cancer type as well as metastatic status. Multivariable logistic regression was performed to determine the adjusted odds ratios (aOR) of in-hospital mortality in different groups. Results: From 5, 936, 014 eligible CV admissions, cancer was present in 265, 221 (4.5%) hospitalizations. There was significant variation in the admission diagnoses among the different cancers, with hematological malignancies being principally associated with heart failure (HF), lung cancer with atrial fibrillation (AF), and colorectal and prostate cancer with acute myocardial infarction (AMI). Admission with haemorrhagic stroke has the highest associated mortality across cancers (20.0–38.4%). In-hospital mortality was higher in cancer than non-cancer patients across most CV admissions ( P  < 0.001) with AF having the worst prognosis. Compared to group without any cancer, the greatest aOR of mortality was associated with lung cancer in AMI (aOR 2.32, 95% CI 2.18–2.47), ischemic stroke (aOR 2.21, 95%CI 2.08–2.34), AF (aOR 4.69, 95%CI 4.32–5.10) and HF (aOR 2.07, 95%CI 1.89–2.27). Conclusions: The most common causes of CV admission to hospital vary in patients with different types of cancer, with AMI being most common in patients with colon cancer, HF in patients with hematological malignancies and AF in patients with lung cancer. Patients with cancer, particularly lung cancer, have greater mortality than non-cancer patients after admissions with a CV cause. Graphical abstract: Unlabelled Image Highlights: The most common cardiovascular causes of hospital admission vary according to cancer type. Cancer patients have increased mortality among the different cardiovascular admission causes, particularly lung cancer. Admission with haemorrhagic stroke showed the highest associated mortality across cancers. Admission with atrial fibrillation carried the worst prognosis across all cancers relative to non-cancer patients.